Risk factors for systemic reactions in typical cold urticaria: Results from the COLD‐CE study. Issue 7 (23rd December 2021) - Bizjak, Mojca; Košnik, Mitja; Dinevski, Dejan; Thomsen, Simon Francis; Fomina, Daria; Borzova, Elena; Kulthanan, Kanokvalai; Meshkova, Raisa; Ahsan, Dalia Melina; Al‐Ahmad, Mona; Altrichter, Sabine; Bauer, Andrea; et al.
Abstract: Background: Cold urticaria (ColdU), that is, the occurrence of wheals or angioedema in response to cold exposure, is classified into typical and atypical forms. The diagnosis of typical ColdU relies on whealing in response to local cold stimulation testing (CST). It can also manifest with cold‐induced anaphylaxis (ColdA). We aimed to determine risk factors for ColdA in typical ColdU. Methods: An international, cross‐sectional study COLD‐CE was carried out at 32 urticaria centers of reference and excellence (UCAREs). Detailed history was taken and CST with an ice cube and/or TempTest ® performed. ColdA was defined as an acute cold‐induced involvement of the skin and/or visible mucosal tissue and at least one of: cardiovascular manifestations, difficulty breathing, or gastrointestinal symptoms. Results: Of 551 ColdU patients, 75% ( n = 412) had a positive CST and ColdA occurred in 37% ( n = 151) of the latter. Cold‐induced generalized wheals, angioedema, acral swelling, oropharyngeal/laryngeal symptoms, and itch of earlobes were identified as signs/symptoms of severe disease. ColdA was most commonly provoked by complete cold water immersion and ColdA caused by cold air was more common in countries with a warmer climate. Ten percent ( n = 40) of typical ColdU patients had a concomitant chronic spontaneous urticaria (CSU). They had a lower frequency of ColdA than those without CSU (4% vs. 39%, p = .003). We identified the following risk factors for cardiovascular manifestations: previous systemic reaction to a Hymenoptera sting, angioedema, oropharyngeal/laryngeal symptoms, and itchy earlobes. Conclusion: ColdA is common in typical ColdU. High‐risk patients require education about their condition and how to use an adrenaline autoinjector. Abstract : The COLD‐CE study was carried out at 32 UCAREs from 19 countries and four continents. Among 551 ColdU patients, 75% had positive local CST (i.e., typical ColdU) and ColdA occurred in 37% of the latter. For the first time, we propose the criteria for adrenaline autoinjector prescription for patients with typical ColdU.Abbreviations: ColdA, cold‐induced anaphylaxis; COLD‐CE, comprehensive evaluation of cold urticaria and other cold‐induced reactions, a study of the GA 2 LEN UCARE network; ColdU, cold urticaria; CST, cold stimulation testing; UCAREs, Urticaria Centers of Reference and Excellence